Toxic Metals in Some Decorative Cosmetics and Nail Products: Analysis, Evaluation, and Mitigation - Meena, Bashdar I.; Tahir, Tara F.; Sdeeq, Shalaw Z.; Sediq, Khalid N. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
Cosmetic marketing is one of the most profitable and fast increasing markets in Kurdistan Region of Iraq. In recent years, the use of cosmetics has witnessed a rapid increase, especially with the emergence of social media and its impact on this trade. The market is full of different cosmetic brands and nail products. Moderate and low-quality brands of cosmetic samples that available in the local markets were selected to investigate their heavy metals and chemical composition. Samples from face foundation, eye shadow, and nail polish products were taken and examined to evaluate the concentration of metals, that is, Hg, Pb, Cd, As, Mn, Cr, Ni, Co, Fe, Zn, Cu, and Al ions, using X-ray diffraction and X-ray fluorescence techniques. The examination results show high concentrations of Fe and Al metals in the lipstick samples whereas the Hg, Cd, Cr, and Ni were out of detection limit. Moreover, the results show contamination of Hg heavy metal in one of the examined nail polishes brands, whereas the rest of foundation and eye shadow samples show a higher concentration of Al and Fe. Curcumin, as a natural bio-friendly chelate, has been used to deplete metal ions using ultraviolet-visible Spectrophotometer.